Comparing Continuous and Intermittent Infusion Effects on Serratus Anterior Plane Blocks in Video-Assisted Thoracoscopic Surgery: A Randomized Clinical Trial - He K; Meng Y; Zhu Y; Wang S; Zong Y (Journal of Pain Research, 2023)
Keqiang He,1,* Yan Meng,1,* Yun Zhu,2 Sheng Wang,1 Yu Zong1 1Department of Anesthesiology, the First Affiliated Hospital of USTC, Division of Life Sciences and Medicine, University of Science and Technology of China, Hefei, People’s Republic of China; 2Department of Radiology, the First Affiliated Hospital of Bengbu Medical College, Bengbu, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yu Zong, Department of Anesthesiology, the First Affiliated Hospital of USTC, Division of Life Sciences and Medicine, University of Science and Technology of China, 17 Lujiang Road, Hefei, Anhui, People’s Republic of China, Email zongyu3540@163.comObjective: The programmed intermittent bolus infusion (PIBI) of local anesthetic produces wider sensory blockade and better analgesia than continuous infusion (CI). We designed this trial to compare the effects of these two different infusion methods combined with Serratus Anterior Plane Blocks (cSAPBs) on postoperative pain relief in patients undergoing video-assisted thoracoscopic surgery.Methods: We randomly allocated 66 patients under going elective video-assisted thoracoscopic unilateral lung resection surgery to two groups (PIBI group and CI group, n=33 per group). After the surgical operation, the patients received ultrasound-guided ipsilateral SAPB, we randomized them to receive either automated intermittent boluses or continuous infusion of 0.3% ropivacaine. Tramadol consumption during the 48 hours following surgery was the primary outcome. Secondary outcomes included cumulative tramadol consumption during the first 24-h and the second 24-h periods after surgery, pain scores, patient satisfaction, blocked dermatomes, and adverse events.Results: During 48h, tramadol consumption in the PIBI group was significantly lower than in the CI group (190 mg [125, 305] vs 220 mg [170, 480], p= 0.034). As compared to the CI group, the PIBI group consumed less tramadol during the first 24 hours (145 mg [87.5, 210] vs 190 mg [140, 400], p=0.012). The dermatomes anesthetized to the pinprick and cold test were significantly more abundant in the PIBI group than in the CI group (3 [3,4] vs. 5 [4,5], p< 0.001). Both groups had similar VAS scores at rest and when moving (p> 0.05). Additionally, the PIBI group showed greater patient satisfaction. Both groups experienced similar adverse events (p> 0.05).Conclusion: Compared with CI, PIBI administration regimen (0.3% ropivacaine 5 mL/h) for cSAPBs resulted in lower tramadol consumption, superior analgesia during the initial 12 h after the operation, and higher patient satisfaction. PIBI combined with cSAPBs was a better choice for postoperative analgesia in patients undergoing video-assisted thoracoscopic surgery.Keywords: continuous serratus anterior plane block, programmed intermittent bolus infusion, video-assisted thoracoscopic surgery, perioperative analgesic therapy